Adhesion film forming material, pattern forming method, and adhesion film forming method
Patent Information
- Application Number
- JP2021209785
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-12-23
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2041-12-23
AI Technical Summary
【0048】 以上説明したように、本発明であれば、レジスト上層膜との高い密着性を有し、微細パターンの倒れ抑止効果を有する密着膜形成材料を提供できる。また、この密着膜形成材料は、高い密着性を有し、微細パターンの倒れ抑止効果を有するとともに、レジスト上層膜のパターン形状、露光感度等を適度に調整することが可能なため、例えば、ケイ素含有中間膜上に該密着膜を形成した4層レジストプロセス、といった多層レジストプロセスにおいて極めて有用である。また、本発明の密着膜の形成方法であれば、被加工基板上で十分に硬化し、かつ、レジスト上層膜との高い密着性を有する密着膜を形成することができる。また、本発明のパターン形成方法であれば、多層レジストプロセスにおいて、被加工基板に微細なパターンを高精度で形成することができる。
Smart Images

Figure 0007634473000052 
Figure 0007634473000053 
Figure 0007634473000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesion film forming material, a pattern forming method, and a method for forming an adhesion film. [Background technology]
[0002] As LSIs become more highly integrated and faster, pattern dimensions are becoming finer. Lithography technology has achieved the formation of fine patterns by shortening the wavelength of light sources and appropriately selecting resist compositions to match them, in line with this miniaturization. The core of this technology is a positive photoresist composition used in a single layer. This single-layer positive photoresist composition has a skeleton in the resist resin that is resistant to dry etching using chlorine- or fluorine-based gas plasma, and has a resist mechanism that dissolves the exposed parts, so that the exposed parts are dissolved to form a pattern, and the remaining resist pattern is used as an etching mask to dry etch the substrate to which the photoresist composition has been applied.
[0003] However, if the thickness of the photoresist film used is kept the same and the pattern width is made smaller, the resolution of the photoresist film decreases, and if the photoresist film is developed into a pattern using a developer, the aspect ratio becomes too large, resulting in pattern collapse. For this reason, the thickness of the photoresist film has been made thinner as the pattern becomes finer.
[0004] On the other hand, in the processing of the substrate to be processed, a method is used in which the substrate to be processed is processed by dry etching using a photoresist film on which a pattern is usually formed as an etching mask, but in reality, there is no dry etching method that can obtain complete etching selectivity between the photoresist film and the substrate to be processed, so that the photoresist film is also damaged during the processing of the substrate to be processed, and the photoresist film collapses during the processing of the substrate to be processed, making it impossible to accurately transfer the resist pattern to the substrate to be processed. Therefore, with the miniaturization of patterns, photoresist compositions are required to have high dry etching resistance. In addition, as the exposure wavelength becomes shorter, the resin used in the photoresist composition is required to have low light absorption at the exposure wavelength, so that in response to the change to i-line, KrF, and ArF, novolac resins, polyhydroxystyrene, and resins with aliphatic polycyclic skeletons have been used. However, in reality, the etching speed under the above dry etching conditions has become fast, and recent photoresist compositions with high resolution tend to have weak etching resistance.
[0005] For this reason, it has become necessary to dry etch the substrate to be processed using a thinner photoresist film with a weaker etching resistance, and securing the materials and processes for this processing step has become an urgent need.
[0006] One method for solving such problems is the multi-layer resist method, in which a resist intermediate film having a different etching selectivity from the photoresist film (i.e., resist upper film) is interposed between the resist upper film and the substrate to be processed, a pattern is obtained in the resist upper film, and then the pattern is transferred to the resist intermediate film by dry etching using the resist upper film pattern as a dry etching mask, and the pattern is further transferred to the substrate to be processed by dry etching using the resist intermediate film as a dry etching mask.
[0007] One of the multilayer resist methods is a three-layer resist method that can be performed using a general resist composition used in a single-layer resist method. In this three-layer resist method, for example, an organic film made of novolac or the like is formed on a substrate to be processed as a resist underlayer film, a silicon-containing film is formed thereon as a silicon-containing resist intermediate film, and a normal organic photoresist film is formed thereon as a resist upper layer film. For dry etching with fluorine-based gas plasma, the organic resist upper layer film has a good etching selectivity to the silicon-containing resist intermediate film, so the resist upper layer film pattern is transferred to the silicon-containing resist intermediate film by using dry etching with fluorine-based gas plasma. Furthermore, for etching with oxygen gas or hydrogen gas, the silicon-containing resist intermediate film can have a good etching selectivity to the resist underlayer film, so the silicon-containing resist intermediate film pattern is transferred to the resist underlayer film by etching with oxygen gas or hydrogen gas. According to this method, even if a photoresist composition is used that is difficult to form a pattern with a sufficient film thickness for directly processing a substrate to be processed, or a photoresist composition that does not have sufficient dry etching resistance for processing a substrate, if a pattern can be transferred to a silicon-containing film (silicon-containing resist intermediate film), a pattern of an organic film (resist underlayer film) made of novolak or the like that has sufficient dry etching resistance for processing can be obtained.
[0008] In recent years, 13.5 nm wavelength vacuum ultraviolet (EUV) lithography has been attracting attention as a promising technology to replace the combined use of ArF immersion lithography and multiple exposure processes. Using this technology, it has become possible to form fine patterns with a half pitch of 25 nm or less in a single exposure.
[0009] On the other hand, in EUV lithography, there is a strong demand for high sensitivity in resist materials to compensate for the insufficient output of the light source. However, the increase in shot noise that accompanies high sensitivity leads to an increase in edge roughness (LER, LWR) of the line pattern, and therefore achieving both high sensitivity and low edge roughness is one of the important challenges in EUV lithography.
[0010] In recent years, the use of metal materials in resist materials has been considered as an attempt to increase the sensitivity of resists and reduce the effects of shot noise. Compounds containing metal elements such as barium, titanium, hafnium, zirconium, and tin have a higher absorbance to EUV light than organic materials that do not contain metals, and are expected to improve the photosensitivity of resists and suppress the effects of shot noise. In addition, metal-containing resist patterns can be combined with an underlayer film made of a non-metallic material to enable high-selectivity etching processing.
[0011] For example, resist materials containing added metal salts or organometallic complexes (Patent Documents 1 and 2) and non-chemically amplified resist materials using metal oxide nanoparticles (Patent Document 3 and Non-Patent Document 1) have been investigated. However, the resolution of these metal-containing resists has not yet reached the level required for practical use, and further improvement in resolution is required.
[0012] Furthermore, ArF immersion lithography Rough With the advent of lithography, EUV lithography, etc., it is becoming possible to form finer patterns, but on the other hand, ultra-fine patterns are extremely prone to collapse due to their small contact area, and suppressing pattern collapse is a major issue. Recently, it is said that the interaction at the interface between the resist top layer film and the resist bottom layer film in fine patterns affects pattern collapse, and there is a need to improve the performance of the resist bottom layer film.
[0013] In order to suppress pattern collapse, materials have been reported that improve adhesion to a resist upper layer film by using a resist underlayer film containing a polar functional group such as a lactone structure or a urea structure (Patent Documents 4 and 5). However, in the current situation where finer pattern formation is required, it cannot be said that these materials have sufficient pattern collapse suppression performance. For the above reasons, materials with higher pattern collapse suppression performance and adhesion are required. [Prior art documents] [Patent documents]
[0014] [Patent Document 1] Patent No. 5708521 [Patent Document 2] Patent No. 5708522 [Patent Document 3] U.S. Patent No. 9,310,684 [Patent Document 4] International Publication No. 2003 / 017002 [Patent Document 5] International Publication No. 2018 / 143359 [Patent Document 6] Patent No. 5415982 [Non-patent literature]
[0015] [Non-Patent Document 1] Proc. SPIE Vol. 7969, 796915 (2011) Summary of the Invention [Problem to be solved by the invention]
[0016] The present invention has been made in consideration of the above circumstances, and has an object to provide an adhesion film forming material that provides an adhesion film that has high adhesion to an overlying resist film, has an effect of preventing collapse of a fine pattern, and is capable of forming a good pattern shape in a fine patterning process using a multilayer resist method in a semiconductor device manufacturing process, a pattern formation method using the material, and a method for forming the adhesion film. [Means for solving the problem]
[0017] In order to solve the above problems, the present invention provides an adhesion film-forming material used for an adhesion film formed directly under a resist upper layer film, the adhesion film-forming material comprising: (A) a resin having at least one structural unit containing a fluorine-substituted organic sulfonyl anion structure and having at least one structural unit represented by the following general formula (2) apart from the structural unit containing a fluorine-substituted organic sulfonyl anion structure; (B) a thermal acid generator; and (C) an organic solvent. [ka] (In the above general formula (2), R6 is a hydrogen atom or a methyl group, and R7 is a group selected from the following formulae (2-1) to (2-3).) [ka] (In the above formula, the dashed lines represent bonds.)
[0018] Such an adhesive film-forming material can form an adhesive film that has high adhesion to the resist upper layer film, has the effect of preventing the fine pattern from collapsing, and gives a good pattern shape.
[0019] In the present invention, the fluorine-substituted organic sulfonyl anion structure is preferably a structure represented by the following general formula (1). [ka] (In the formula, R1 is a hydrogen atom or a methyl group. R2 is a single bond, -Z 21 -C(=O)-O-, -Z 21 -O- or -Z 21 -OC(=O)-, Z 21is a saturated hydrocarbylene group having 1 to 12 carbon atoms, which may contain a carbonyl group, an ester bond or an ether bond. R3 to R5 are each independently a hydrocarbyl group having 1 to 21 carbon atoms which may contain a heteroatom. Any two of R3, R4 and R5 may be bonded to each other to form a ring together with the sulfur atom to which they are bonded. A1 is a hydrogen atom or a trifluoromethyl group.
[0020] Furthermore, in the present invention, it is more preferable that R2 in the general formula (1) contains a divalent organic group having an alicyclic structure.
[0021] Such an adhesive film-forming material can form an adhesive film that has higher adhesion to the resist upper layer film, has a higher effect of preventing collapse of the fine pattern, and gives a better pattern shape.
[0022] In the present invention, the (C) organic solvent is preferably a mixture of one or more organic solvents having a boiling point of less than 150°C and one or more organic solvents having a boiling point of 150°C or more and less than 220°C.
[0023] Such an adhesive film-forming material has excellent film-forming properties and sufficient solvent solubility, making it possible to suppress the occurrence of coating defects.
[0024] In the present invention, the weight average molecular weight of the (A) resin is preferably 5,000 to 70,000.
[0025] An adhesive film-forming material containing a resin having a weight-average molecular weight in this range has excellent film-forming properties, and can suppress the generation of sublimates during heat curing, thereby preventing contamination of the device due to the sublimates.
[0026] In the present invention, it is preferable to further contain at least one of (D) a photoacid generator, (E) a surfactant, (F) a crosslinking agent, and (G) a plasticizer.
[0027] The presence or absence / selection of these various additives makes it possible to fine-tune the performance in accordance with customer requirements, such as film-forming properties, embedding properties, optical properties, and reduction of sublimation products, which is preferable from a practical standpoint.
[0028] In the present invention, it is preferable that the resist upper layer film is formed using a negative resist composition.
[0029] Furthermore, in the present invention, it is more preferable that the resist upper layer film is formed using a resist upper layer film material containing at least an organometallic compound and a solvent.
[0030] Furthermore, the organometallic compound may contain titanium, cobalt, copper, zinc, zirconium, lead, indium, tin, antimony, and hafnium It is more preferable that the composition includes at least one selected from the following:
[0031] Such an adhesive film-forming material has an effect of suppressing collapse of a fine pattern, and can appropriately adjust the pattern shape, exposure sensitivity, etc. of the resist top layer film. At the same time, it can prevent contamination of the processed substrate by metal compounds when using a resist top layer film material containing an organometallic compound and a solvent.
[0032] The present invention also provides a method for forming a pattern on a substrate to be processed, comprising the steps of: (I-1) A step of applying the above-described adhesive film-forming material onto a substrate to be processed, followed by heat treatment to form an adhesive film; (I-2) forming a resist top layer film on the adhesion film using a photoresist material; (I-3) a step of forming a circuit pattern on the resist upper layer film by pattern-exposing the resist upper layer film and then developing the resist upper layer film with a developer; (I-4) a step of transferring the pattern to the adhesive film by dry etching using the resist upper layer film on which the circuit pattern is formed as a mask; and (I-5) a step of processing the substrate to be processed using the adhesive film to which the pattern has been transferred as a mask to form a pattern on the substrate to be processed; The present invention provides a pattern forming method comprising the steps of:
[0033] The present invention also provides a method for forming a pattern on a workpiece substrate, comprising the steps of: (II-1) forming a resist underlayer film on a substrate to be processed; (II-2) forming a silicon-containing resist intermediate film on the resist underlayer film; (II-3) a step of applying the above-described adhesion film-forming material onto the silicon-containing resist intermediate film, followed by heat treatment to form an adhesion film; (II-4) forming a resist top layer film on the adhesion film using a photoresist material; (II-5) a step of forming a circuit pattern on the resist upper layer film by pattern-exposing the resist upper layer film and then developing the resist upper layer film with a developer; (II-6) a step of transferring the pattern to the adhesive film by dry etching using the resist upper layer film on which the circuit pattern is formed as a mask; (II-7) a step of transferring the pattern to the silicon-containing resist intermediate film by dry etching using the adhesion film on which the pattern is formed as a mask; (II-8) a step of transferring a pattern to the resist underlayer film by dry etching using the silicon-containing resist intermediate film to which the pattern has been transferred as a mask; and (II-9) a step of processing the substrate using the resist underlayer film to which the pattern has been transferred as a mask to form a pattern on the substrate; The present invention provides a pattern forming method comprising the steps of:
[0034] The present invention also provides a method for forming a pattern on a workpiece substrate, comprising the steps of: (III-1) forming a resist underlayer film on a substrate to be processed; (III-2) forming an inorganic hard mask intermediate film selected from a silicon oxide film, a silicon nitride film, and a silicon oxynitride film on the resist underlayer film; (III-3) A step of forming an adhesion film by applying the above-described adhesion film forming material onto the inorganic hard mask intermediate film and then performing a heat treatment; (III-4) forming a resist top layer film on the adhesion film using a photoresist material; (III-5) a step of forming a circuit pattern on the resist upper layer film by pattern-exposing the resist upper layer film and then developing the resist upper layer film with a developer; (III-6) a step of transferring the pattern to the adhesive film by dry etching using the resist upper layer film on which the circuit pattern has been formed as a mask; (III-7) a step of transferring the pattern to the inorganic hard mask intermediate film by dry etching using the adhesive film on which the pattern is formed as a mask; (III-8) a step of transferring a pattern to the resist underlayer film by dry etching using the inorganic hard mask intermediate film to which the pattern has been transferred as a mask; and (III-9) a step of processing the substrate using the resist underlayer film to which the pattern has been transferred as a mask to form a pattern on the substrate; The present invention provides a pattern forming method comprising the steps of:
[0035] In this way, the adhesion film forming material of the present invention can be suitably used in various pattern formation methods, such as a two-layer resist process or a four-layer resist process in which the adhesion film is formed on a silicon-containing intermediate film (silicon-containing resist intermediate film, inorganic hard mask intermediate film). In these pattern formation methods, the formation of an adhesion film can effectively reduce pattern collapse, and the material is suitable for photolithography of a resist upper layer film.
[0036] In this case, it is preferable that the inorganic hard mask intermediate film is formed by a CVD method or an ALD method.
[0037] In the present invention, the method for forming a circuit pattern on the resist upper layer film is preferably photolithography with a wavelength of 10 nm or more and 300 nm or less, direct writing with an electron beam, nanoimprinting, or a combination of these.
[0038] In the present invention, the developing method is preferably alkaline developing or developing with an organic solvent.
[0039] In the present invention, by using the above-mentioned pattern formation method, the pattern can be formed satisfactorily and efficiently.
[0040] In addition, in the present invention, it is preferable to use, as the substrate to be processed, a semiconductor device substrate, or a semiconductor device substrate having any one of a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal oxide carbide film, and a metal oxide nitride film formed thereon.
[0041] In this case, the metal is preferably silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum, or an alloy thereof.
[0042] According to the pattern forming method of the present invention, the above-mentioned substrate to be processed can be processed as described above to form a pattern.
[0043] The present invention also provides a method for forming an adhesion film that functions as an adhesion layer used in the manufacturing process of a semiconductor device, which comprises spin-coating the adhesion film-forming material described above on a substrate to be processed, and heat-treating the substrate coated with the adhesion film-forming material at a temperature of 100°C or higher and 300°C or lower for 10 to 600 seconds to form a hardened film.
[0044] The present invention also provides a method for forming an adhesion film that functions as an adhesion layer used in the manufacturing process of a semiconductor device, which comprises spin-coating the adhesion film-forming material described above onto a substrate to be processed, and heat-treating the substrate coated with the adhesion film-forming material in an atmosphere having an oxygen concentration of 0.1% or more and 21% or less to form a hardened film.
[0045] By using such a method, the crosslinking reaction during the formation of the adhesive film can be promoted, and mixing with the resist upper layer film can be more effectively suppressed. In addition, by appropriately adjusting the heat treatment temperature, time, and oxygen concentration within the above ranges, it is possible to obtain an effect of suppressing the collapse of the pattern of the adhesive film suitable for the application, and to obtain the pattern shape adjustment property of the resist upper layer film.
[0046] The present invention also provides a method for forming an adhesion film that functions as an adhesion layer used in the manufacturing process of a semiconductor device, which comprises spin-coating the adhesion film-forming material described above onto a substrate to be processed, and heat-treating the substrate coated with the adhesion film-forming material in an atmosphere with an oxygen concentration of less than 0.1%, thereby forming a hardened film.
[0047] This method is useful because it promotes the crosslinking reaction during the formation of the adhesion film and more highly suppresses intermixing with the overlying film without causing deterioration of the substrate to be processed, even if the substrate contains a material that is unstable when heated in an oxygen atmosphere. Effect of the Invention
[0048] As described above, the present invention can provide an adhesive film-forming material that has high adhesion to the resist top layer film and has a fine pattern collapse suppressing effect. In addition, this adhesive film-forming material has high adhesion and has a fine pattern collapse suppressing effect, and can appropriately adjust the pattern shape and exposure sensitivity of the resist top layer film, so it is extremely useful in a multi-layer resist process, such as a four-layer resist process in which the adhesive film is formed on a silicon-containing intermediate film. In addition, the adhesive film forming method of the present invention can form an adhesive film that is sufficiently cured on the substrate to be processed and has high adhesion to the resist top layer film. In addition, the pattern forming method of the present invention can form a fine pattern on the substrate to be processed with high precision in the multi-layer resist process. [Brief description of the drawings]
[0049] [Figure 1]FIG. 2 is an explanatory diagram of an example of a pattern forming method using a four-layer resist process of the present invention. [Diagram 2] FIG. 2 is an explanatory diagram showing a method for measuring adhesion in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0050] When an element is said to be "directly below" another element, it is in direct contact with the other element and there are no intervening elements. In contrast, when an element is said to be "under" another element, there may be intervening elements between them. Similarly, when an element is said to be "directly on" another element, it is in direct contact with the other element and there are no intervening elements, and when an element is said to be "on" another element, there may be intervening elements between them.
[0051] As described above, in the fine patterning process using the multilayer resist method in the semiconductor device manufacturing process, there has been a demand for an adhesion film forming material that has high adhesion to an overlying resist film and has an effect of preventing the collapse of a fine pattern, a pattern formation method using said material, and a method for forming an adhesion film.
[0052] Until now, resist underlayer film materials containing a resin having, as a repeating unit, a (meth)acrylic ester that generates α-fluorosulfonic acid bonded to the main chain by light and / or heat have been used as resist underlayer film materials. pattern It has been shown to be effective in improving the adhesion between the shape and the resist (Patent Document 6). In this invention, alpha-fluorosulfonic acid derived from the resist underlayer film is present at the bottom of the resist film, which is said to prevent the acid from being deactivated in the film, thereby preventing footing after development and scum in the space. However, the application of this invention is limited to positive resists, and its effect on negative resists in particular has not been clarified.
[0053] In a pattern obtained by negative development (hereafter referred to as a negative pattern), when the film quality of the photoresist film before exposure is compared with that of the negative pattern after exposure, the acid labile groups in the negative pattern are released by the acid generated by exposure, resulting in an increased amount of hydrophilic groups such as carboxyl groups and phenolic hydroxyl groups.
[0054] Therefore, the present inventors thought that by using a resin that generates sulfonic acid bonded to the main chain, the sulfonic acid would form hydrogen bonds with the above-mentioned carboxyl group or phenolic hydroxyl group, and an adhesive film that is particularly excellent in adhesion to negative patterns could be developed. As a result of intensive research, the inventors found that an adhesive film-forming material mainly composed of a compound with a specific structure, a pattern formation method using the material, and a method for forming an adhesive film are very effective, and thus completed the present invention.
[0055] That is, the present invention provides an adhesion film-forming material used for an adhesion film formed directly under a resist upper layer film, the adhesion film-forming material comprising: (A) a resin having at least one structural unit containing a fluorine-substituted organic sulfonyl anion structure and having at least one structural unit represented by the following general formula (2) in addition to the structural unit containing the fluorine-substituted organic sulfonyl anion structure; (B) a thermal acid generator; and (C) an organic solvent. [ka] (In the above general formula (2), R6 is a hydrogen atom or a methyl group, and R7 is a group selected from the following formulae (2-1) to (2-3).) [ka] (In the above formula, the dashed lines represent bonds.)
[0056] The present invention will be described in detail below, but the present invention is not limited thereto.
[0057] [Adhesive film forming materials] The present invention provides an adhesion film-forming material used for an adhesion film formed directly under a resist upper layer film, the adhesion film-forming material comprising: (A) a resin having at least one structural unit containing a fluorine-substituted organic sulfonyl anion structure and having at least one structural unit represented by the following general formula (2) apart from the structural unit containing a fluorine-substituted organic sulfonyl anion structure; (B) a thermal acid generator; and (C) an organic solvent. [ka] (In the above general formula (2), R6 is a hydrogen atom or a methyl group, and R7 is a group selected from the following formulae (2-1) to (2-3).) [ka] (In the above formula, the dashed lines represent bonds.)
[0058] In the adhesive film-forming material of the present invention, the (A) resin may be used alone or in combination of two or more. Furthermore, the adhesive film-forming material may contain components other than the above components (A) to (C). Each component will be described below.
[0059] [(A) Resin] The (A) resin contained in the adhesion film-forming material of the present invention has at least one structural unit containing a fluorine-substituted organic sulfonyl anion structure, and has at least one structural unit represented by the following general formula (2) in addition to the structural unit containing a fluorine-substituted organic sulfonyl anion structure. [ka] (In the above general formula (2), R6 is a hydrogen atom or a methyl group, and R7 is a group selected from the following formulae (2-1) to (2-3).) [ka] (In the above formula, the dashed lines represent bonds.)
[0060] The fluorine-substituted organic sulfonyl anion structure is preferably a structure represented by the following general formula (1), but is not limited thereto. [ka] (In the formula, R1 is a hydrogen atom or a methyl group. R2 is a single bond, -Z 21 -C(=O)-O-, -Z 21 -O- or -Z 21 -OC(=O)-, Z 21 is a saturated hydrocarbylene group having 1 to 12 carbon atoms, which may contain a carbonyl group, an ester bond or an ether bond. R3 to R5 are each independently a hydrocarbyl group having 1 to 21 carbon atoms which may contain a heteroatom. Any two of R3, R4 and R5 may be bonded to each other to form a ring together with the sulfur atom to which they are bonded. A1 is a hydrogen atom or a trifluoromethyl group.
[0061] In the above general formula (1), R2 is -Z 21 -C(=O)-O-, -Z 21 -O- or -Z 21 -OC(=O)-, Z 21 Specific examples of the saturated hydrocarbylene group having 1 to 12 carbon atoms which may contain a carbonyl group, an ester bond or an ether bond, include, but are not limited to, the following:
[0062] [ka] (In the formula, the dashed lines represent bonds.)
[0063] It is preferable that R2 in the general formula (1) contains a divalent organic group having an alicyclic structure.
[0064] The structural unit represented by the general formula (1) functions as an acid generating group. This structural unit generates sulfonic acid, which forms hydrogen bonds with the pattern, improving adhesion to the resist. In addition, since the generated acid is bonded to the polymer main chain, deterioration of the resist upper layer film, such as pattern roughness, caused by excessive acid diffusion, can be prevented.
[0065] Specific examples of the anion of the monomer that gives the above general formula (1) include, but are not limited to, the following: In the following formula, R1 is the same as above. [ka]
[0066] [ka]
[0067] Examples of the cations of the monomers which give the above general formula (1) include triphenylsulfonium, 4-hydroxyphenyldiphenylsulfonium, bis(4-hydroxyphenyl)phenylsulfonium, tris(4-hydroxyphenyl)sulfonium, 4-tert-butoxyphenyldiphenylsulfonium, bis(4-tert-butoxyphenyl)phenylsulfonium, tris(4-tert-butoxyphenyl)sulfonium, 3-tert-butoxyphenyldiphenylsulfonium, bis(3-tert-butoxyphenyl) phenyl)phenylsulfonium, tris(3-tert-butoxyphenyl)sulfonium, 3,4-di-tert-butoxyphenyldiphenylsulfonium, bis(3,4-di-tert-butoxyphenyl)phenylsulfonium, tris(3,4-di-tert-butoxyphenyl)sulfonium, diphenyl(4-thiophenoxyphenyl)sulfonium, 4-tert-butoxycarbonylmethyloxyphenyldiphenylsulfonium, tris(4-tert-butoxycarbonylmethyloxyphenyl)sulfonium , (4-tert-butoxyphenyl)bis(4-dimethylaminophenyl)sulfonium, tris(4-dimethylaminophenyl)sulfonium, 2-naphthyldiphenylsulfonium, (4-hydroxy-3,5-dimethylphenyl)diphenylsulfonium, (4-n-hexyloxy-3,5-dimethylphenyl)diphenylsulfonium, dimethyl(2-naphthyl)sulfonium, 4-hydroxyphenyldimethylsulfonium, 4-methoxyphenyldimethylsulfonium, trimethylsulfonium, 2-naphthyldiphenylsulfonium, Examples of such sulfonyl groups include 2-oxo-2-phenylethylthiacyclopentanium, diphenyl 2-thienylsulfonium, 4-n-butoxynaphthyl-1-thiacyclopentanium, 2-n-butoxynaphthyl-1-thiacyclopentanium, 4-methoxynaphthyl-1-thiacyclopentanium, and 2-methoxynaphthyl-1-thiacyclopentanium.More preferred are triphenylsulfonium, 4-tert-butylphenyldiphenylsulfonium, 4-tert-butoxyphenyldiphenylsulfonium, tris(4-tert-butylphenyl)sulfonium, tris(4-tert-butoxyphenyl)sulfonium, dimethylphenylsulfonium, etc. Further examples include those represented by the following structures, but are not limited to these.
[0068] [ka]
[0069] The structural unit represented by the general formula (2) functions as a crosslinking group, and can impart curability without impairing the adhesion between the resist upper layer film and the substrate to be processed or the silicon-containing intermediate film, due to the interaction of the hydroxyl group generated by the ring-opening reaction that occurs during curing of the epoxy or oxetane structure.
[0070] Specific examples of the structural unit represented by the general formula (2) include the following: R6 is the same as above. [ka]
[0071] In addition, the (A) resin contained in the adhesion film-forming material of the present invention preferably has structural units represented by the above general formulas (1) and (2) as structural units, and the structural units represented by the above general formulas (1) and (2) may be used singly or in combination of two or more.
[0072] Combining a plurality of structural units not only improves adhesion and enhances the effect of preventing collapse of fine patterns, but also makes it possible to appropriately adjust the pattern shape, exposure sensitivity, etc. of the resist upper layer film.
[0073] Furthermore, in the present invention, the molar fraction of the structural unit represented by the above general formula (1) in the (A) resin is preferably 5% to 50%, more preferably 5% to 30%. The molar fraction of the structural unit represented by the above general formula (2) is preferably 30% to 95%, more preferably 40% to 90%. By combining structural units in such a range, it is possible to impart adhesion while maintaining curability.
[0074] In addition, when the molar fractions of the structural units represented by the above general formulas (1) and (2) do not total 100%, the resin (A) contains other structural units. In such cases, the other structural units include α,β-unsaturated carboxylic acid esters such as other acrylic acid esters, other methacrylic acid esters, other acrylic acid amides, other methacrylic acid amides, crotonate esters, maleate esters, and itaconic acid esters; α,β-unsaturated carboxylic acids such as methacrylic acid, acrylic acid, maleate, and itaconic acid; acrylonitrile; methacrylonitrile; α,β-unsaturated lactones such as 5,5-dimethyl-3-methylene-2-oxotetrahydrofuran; norbornene derivatives, tetracyclo[4.4.0.1 2,5 .1 7,10 Any of structural units derived from cyclic olefins such as ]dodecene derivatives; α,β-unsaturated carboxylic anhydrides such as maleic anhydride and itaconic anhydride; allyl ethers; vinyl ethers; vinyl esters; and vinyl silanes can be used in combination.
[0075] Adhesion film-forming materials containing these resins can form adhesion film-forming materials that have high adhesion to the resist overcoat film and have the effect of preventing the collapse of fine patterns, and can be easily manufactured.
[0076] By using an adhesion film-forming material containing such a resin in the formation of a multilayer resist film that is applied to fine processing in the manufacturing process of a semiconductor device or the like, it is possible to provide an adhesion film-forming material for forming an adhesion film that has high adhesion to an overlying resist film and has the effect of preventing collapse of a fine pattern, a method for forming an adhesion film, and a method for forming a pattern.
[0077] The resin can be synthesized by polymerizing each monomer protected by a protecting group as necessary by a known method, and then carrying out a deprotection reaction as necessary. The polymerization reaction is not particularly limited, but is preferably radical polymerization or anionic polymerization. For these methods, JP-A-2004-115630 can be referred to.
[0078] The resin preferably has a weight average molecular weight (Mw) of 5,000 to 70,000, more preferably 15,000 to 50,000. If Mw is 5,000 or more, the resin has excellent film-forming properties, and can suppress the generation of sublimates during heat curing, thereby suppressing contamination of the device due to the sublimates. On the other hand, if Mw is 70,000 or less, the resin can suppress the occurrence of poor coating properties and coating defects due to insufficient solubility in a solvent. The resin also preferably has a molecular weight distribution (Mw / Mn) of 1.0 to 2.8, more preferably 1.0 to 2.5. In the present invention, Mw and molecular weight distribution are values measured in terms of polystyrene by gel permeation chromatography (GPC) using tetrahydrofuran (THF) as a solvent.
[0079] [(B) Thermal acid generator] In the adhesive film-forming material of the present invention, a thermal acid generator (B) is added in order to promote the crosslinking reaction by heat.
[0080] The thermal acid generator (B) that can be used in the organic film material for manufacturing a semiconductor device of the present invention is Examples include the following general formula (3).
[0081] [ka] (In the formula, K - R8, R9, R 10 and R 11 Each represents a hydrogen atom or a linear, branched or cyclic alkyl group, alkenyl group, oxoalkyl group or oxoalkenyl group having 1 to 12 carbon atoms, an aryl group having 6 to 20 carbon atoms, or an aralkyl group or aryloxoalkyl group having 7 to 12 carbon atoms, and some or all of the hydrogen atoms of these groups may be substituted with an alkoxy group or the like. 10 may form a ring, and when a ring is formed, R and R and R and R 10 represents an alkylene group having 3 to 10 carbon atoms, or a heteroaromatic ring having a nitrogen atom in the ring.
[0082] Above, R8, R9, R 10 and R 11may be the same or different, and specific examples of the alkyl group include methyl, ethyl, propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, pentyl, hexyl, heptyl, octyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclopropylmethyl, 4-methylcyclohexyl, cyclohexylmethyl, norbornyl, and adamantyl. Examples of the alkenyl group include vinyl, allyl, propenyl, butenyl, hexenyl, and cyclohexenyl. Examples of the oxoalkyl group include 2-oxocyclopentyl, 2-oxocyclohexyl, 2-oxopropyl, 2-cyclopentyl-2-oxoethyl, 2-cyclohexyl-2-oxoethyl, and 2-(4-methylcyclohexyl)-2-oxoethyl. Examples of the oxoalkenyl group include a 2-oxo-4-cyclohexenyl group and a 2-oxo-4-propenyl group. Examples of the aryl group include a phenyl group, a naphthyl group, and the like; alkoxyphenyl groups such as a p-methoxyphenyl group, a m-methoxyphenyl group, an o-methoxyphenyl group, an ethoxyphenyl group, a p-tert-butoxyphenyl group, and a m-tert-butoxyphenyl group; alkylphenyl groups such as a 2-methylphenyl group, a 3-methylphenyl group, a 4-methylphenyl group, an ethylphenyl group, a 4-tert-butylphenyl group, a 4-butylphenyl group, and a dimethylphenyl group; alkylnaphthyl groups such as a methylnaphthyl group and an ethylnaphthyl group; alkoxynaphthyl groups such as a methoxynaphthyl group and an ethoxynaphthyl group; dialkylnaphthyl groups such as a dimethylnaphthyl group and a diethylnaphthyl group; and dialkoxynaphthyl groups such as a dimethoxynaphthyl group and a diethoxynaphthyl group. Examples of the aralkyl group include a benzyl group, a phenylethyl group, a phenethyl group, etc. Examples of the aryloxoalkyl group include a 2-aryl-2-oxoethyl group such as a 2-phenyl-2-oxoethyl group, a 2-(1-naphthyl)-2-oxoethyl group, and a 2-(2-naphthyl)-2-oxoethyl group.
[0083] Also, R8, R9, R 10 , R 11Examples of the heteroaromatic ring having a nitrogen atom in the ring include imidazole derivatives (e.g., imidazole, 4-methylimidazole, 4-methyl-2-phenylimidazole, etc.), pyrazole derivatives, furazan derivatives, pyrroline derivatives (e.g., pyrroline, 2-methyl-1-pyrroline, etc.), pyrrolidine derivatives (e.g., pyrrolidine, N-methylpyrrolidine, pyrrolidinone, N-methylpyrrolidone, etc.), imidazoline derivatives, imidazolidine derivatives, pyridine derivatives (e.g., pyridine, methylpyridine, ethylpyridine, propylpyridine, butylpyridine, 4-(1-butylpentyl)pyridine, dimethylpyridine, trimethylpyridine, triethylpyridine, phenylpyridine, 3-methyl-2-phenylpyridine, 4-tert-butylpyridine, diphenylpyridine, benzylpyridine, methoxypyridine, butoxypyridine, dimethoxypyridine, 1-methyl-2-pyridone, Examples include 4-pyrrolidinopyridine, 1-methyl-4-phenylpyridine, 2-(1-ethylpropyl)pyridine, aminopyridine, dimethylaminopyridine, etc.), pyridazine derivatives, pyrimidine derivatives, pyrazine derivatives, pyrazoline derivatives, pyrazolidine derivatives, piperidine derivatives, piperazine derivatives, morpholine derivatives, indole derivatives, isoindole derivatives, 1H-indazole derivatives, indoline derivatives, quinoline derivatives (e.g., quinoline, 3-quinolinecarbonitrile, etc.), isoquinoline derivatives, cinnoline derivatives, quinazoline derivatives, quinoxaline derivatives, phthalazine derivatives, purine derivatives, pteridine derivatives, carbazole derivatives, phenanthridine derivatives, acridine derivatives, phenazine derivatives, 1,10-phenanthroline derivatives, adenine derivatives, adenosine derivatives, guanine derivatives, guanosine derivatives, uracil derivatives, uridine derivatives, and the like.
[0084] Above, K. -Examples of the non-nucleophilic counter ion include halide ions such as chloride ion and bromide ion; fluoroalkyl sulfonates such as triflate, 1,1,1-trifluoroethanesulfonate, and nonafluorobutanesulfonate; aryl sulfonates such as tosylate, benzenesulfonate, 4-fluorobenzenesulfonate, and 1,2,3,4,5-pentafluorobenzenesulfonate; alkyl sulfonates such as mesylate and butanesulfonate; imide acids such as bis(trifluoromethylsulfonyl)imide, bis(perfluoroethylsulfonyl)imide, and bis(perfluorobutylsulfonyl)imide; methide acids such as tris(trifluoromethylsulfonyl)methide and tris(perfluoroethylsulfonyl)methide; and sulfonates having a fluoro-substituted α-position as shown in the following general formula (4) and sulfonates having a fluoro-substituted α-position as shown in the following general formula (5).
[0085] [ka]
[0086] [ka]
[0087] In the above general formula (4), R 12 is a hydrogen atom, a linear, branched, or cyclic alkyl group having 1 to 23 carbon atoms, an acyl group, an alkenyl group having 2 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, or an aryloxy group. 13 is a hydrogen atom, a linear, branched, or cyclic alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, or an aryl group having 6 to 20 carbon atoms.
[0088] Specific examples of the thermal acid generator include the following. [ka]
[0089] The thermal acid generator (B) contained in the adhesive film-forming material of the present invention may be used alone or in combination of two or more. The amount of the thermal acid generator added is preferably 0.05 to 30 parts, more preferably 0.1 to 10 parts, based on 100 parts of the resin (A). If it is 0.05 parts or more, the amount of acid generated and the crosslinking reaction are sufficient, and if it is 30 parts or less, there is little risk of a mixing phenomenon occurring due to the acid migrating to the upper resist layer.
[0090] [(C) Organic solvent] The (C) organic solvent contained in the adhesion film forming material used in the adhesion film forming method of the present invention is not particularly limited as long as it dissolves the (A) resin, (B) thermal acid generator, and other additives, if any, but is preferably a mixture of one or more organic solvents having a boiling point of less than 150° C. and one or more organic solvents having a boiling point of 150° C. or more and less than 220° C. Specifically, the organic solvents may be ketones such as cyclohexanone, cyclopentanone, methyl-2-n-pentyl ketone, and 2-heptanone, alcohols such as 3-methoxybutanol, 3-methyl-3-methoxybutanol, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, and diacetone alcohol, propylene glycol monomethyl ether, ethylene glycol monomethyl ether, propylene glycol monoethyl ether, and ethylene glycol monoethyl ether, as described in paragraphs
[0144] and
[0145] of JP-A-2008-111103. Ethers such as ether, propylene glycol dimethyl ether, and diethylene glycol dimethyl ether, esters such as propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, ethyl lactate, ethyl pyruvate, butyl acetate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, tert-butyl acetate, tert-butyl propionate, and propylene glycol monotert-butyl ether acetate, and lactones such as γ-butyrolactone can be used. As organic solvents having a boiling point of less than 150°C, propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, cyclopentanone, and mixtures of two or more of these are preferably used. As organic solvents having a boiling point of 150°C or more and less than 220°C, cyclohexanone, diacetone alcohol, ethyl lactate, γ-butyrolactone, and mixtures of two or more of these are preferably used.
[0091] [Other additives] In addition to the above-mentioned components (A) to (C), the adhesive film-forming material of the present invention may further contain one or more of a photoacid generator (D), a surfactant (E), a crosslinking agent (F), and a plasticizer (G). Each component will be described below.
[0092] [(D) Photoacid generator] In order to appropriately adjust the pattern shape, exposure sensitivity, etc. of the resist upper layer film, a photoacid generator (D) can be added to the adhesive film forming material of the present invention. The photoacid generator can be used alone or in combination of two or more. As the photoacid generator, for example, those described in paragraphs
[0160] to
[0179] of JP2009-126940A can be used. The amount of the photoacid generator added is preferably 0.05 to 30 parts, more preferably 0.1 to 10 parts, based on 100 parts of the resin (A). If the amount of the photoacid generator added is within the above range, the resolution is good and there is no risk of foreign matter problems occurring after resist development or during peeling.
[0093] [(E) Surfactant] To the adhesive film-forming material of the present invention, a surfactant (E) can be added to improve the coating property in spin coating. The surfactant can be used alone or in combination of two or more. As the surfactant, for example, those described in paragraphs
[0142] to
[0147] of JP-A No. 2009-269953 can be used. When a surfactant is added, the amount of the surfactant is preferably 0.001 to 20 parts, more preferably 0.01 to 10 parts, based on 100 parts of the resin (A).
[0094] [(F) Crosslinking agent] In addition, in order to enhance the curing property and further suppress intermixing with the resist upper layer film, a crosslinking agent (F) may be added to the adhesive film forming material of the present invention. The crosslinking agent is not particularly limited, and various known crosslinking agents can be widely used. Examples include melamine-based crosslinking agents, glycoluril-based crosslinking agents, benzoguanamine-based crosslinking agents, urea-based crosslinking agents, β-hydroxyalkylamide-based crosslinking agents, isocyanurate-based crosslinking agents, aziridine-based crosslinking agents, oxazoline-based crosslinking agents, epoxy-based crosslinking agents, and phenol-based crosslinking agents. The (F) crosslinking agent can be used alone or in combination of two or more kinds. When a crosslinking agent is added, the amount of the crosslinking agent is preferably 5 to 50 parts, more preferably 10 to 40 parts, based on 100 parts of the (A) resin. When the amount of the crosslinking agent is 100 parts, the amount of the crosslinking agent is preferably 100 parts to 50 parts, more preferably 10 to 40 parts ... 5 If the amount is 50 parts or less, sufficient curability is exhibited and intermixing with the resist upper layer film can be suppressed. On the other hand, if the amount is 50 parts or less, there is no risk of deterioration in adhesion due to a low ratio of the (A) resin in the composition.
[0095] Specific examples of the melamine-based crosslinking agent include hexamethoxymethylated melamine, hexabutoxymethylated melamine, alkoxy and / or hydroxyl-substituted derivatives thereof, and partial self-condensates thereof. Specific examples of the glycoluril-based crosslinking agent include tetramethoxymethylated glycoluril, tetrabutoxymethylated glycoluril, alkoxy and / or hydroxyl-substituted derivatives thereof, and partial self-condensates thereof. Specific examples of the benzoguanamine-based crosslinking agent include tetramethoxymethylated benzoguanamine, tetrabutoxymethylated benzoguanamine, alkoxy and / or hydroxyl-substituted derivatives thereof, and partial self-condensates thereof. Specific examples of the urea-based crosslinking agent include dimethoxymethylated dimethoxyethyleneurea, alkoxy and / or hydroxyl-substituted derivatives thereof, and partial self-condensates thereof. Specific examples of the β-hydroxyalkylamide-based crosslinking agent include N,N,N',N'-tetra(2-hydroxyethyl)adipic acid amide. Specific examples of isocyanurate crosslinking agents include triglycidyl isocyanurate and triallyl isocyanurate. Specific examples of aziridine crosslinking agents include 4,4'-bis(ethyleneiminocarbonylamino)diphenylmethane and 2,2-bishydroxymethylbutanol-tris[3-(1-aziridinyl)propionate]. Specific examples of oxazoline crosslinking agents include 2,2'-isopropylidenebis(4-benzyl-2-oxazoline) and 2,2'-isopropylidenebis(4-phenyl-2-oxazoline). 、2Examples of epoxy crosslinking agents include diglycidyl ether, ethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, poly(glycidyl methacrylate), trimethylolethane triglycidyl ether, trimethylolpropane triglycidyl ether, and pentaerythritol tetraglycidyl ether.
[0096] A specific example of the phenol-based crosslinking agent is a compound represented by the following general formula (6). [ka] (In the formula, Q is a single bond or a q-valent hydrocarbon group having 1 to 20 carbon atoms. R 14 is a hydrogen atom or an alkyl group having 1 to 20 carbon atoms. q is an integer of 1 to 5.
[0097] Q is a single bond or a q-valent hydrocarbon group having 1 to 20 carbon atoms. q is an integer of 1 to 5, and is more preferably 2 or 3. Specific examples of Q include methane, ethane, propane, butane, isobutane, pentane, cyclopentane, hexane, cyclohexane, methylpentane, methylcyclohexane, dimethylcyclohexane, trimethylcyclohexane, benzene, toluene, xylene, ethylbenzene, ethylisopropylbenzene, diisopropylbenzene, methylnaphthalene, ethylnaphthalene, and eicosane. R 14is a hydrogen atom or an alkyl group having 1 to 20 carbon atoms. Specific examples of the alkyl group having 1 to 20 carbon atoms include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a pentyl group, an isopentyl group, a hexyl group, an octyl group, an ethylhexyl group, a decyl group, and an eicosanyl group, and a hydrogen atom or a methyl group is preferable.
[0098] Specific examples of the compound represented by the above general formula (6) include the following compounds. Among these, from the viewpoint of improving the curability and thickness uniformity of the adhesive film, hexamethoxymethylated products of triphenolmethane, triphenolethane, 1,1,1-tris(4-hydroxyphenyl)ethane, and tris(4-hydroxyphenyl)-1-ethyl-4-isopropylbenzene are preferred. [ka]
[0099] [ka]
[0100] The (F) crosslinking agent can be used alone or in combination of two or more. The amount of the (F) crosslinking agent added is preferably 10% by mass to 50% by mass, more preferably 15% by mass to 30% by mass, based on 100 parts of the (A) resin. If the amount added is 10% by mass or more, sufficient curability is obtained and intermixing with the resist upper layer film can be suppressed. On the other hand, if the amount added is 50% by mass or less, the ratio of the (A) resin in the composition is not reduced, and there is no risk of deterioration of adhesion.
[0101] [(G) Plasticizer] In addition, a plasticizer can be added to the adhesive film forming material of the present invention. The plasticizer is not particularly limited, and various known plasticizers can be widely used. Examples include low molecular weight compounds such as phthalates, adipic esters, phosphates, trimellitates, and citrates, and polymers such as polyethers, polyesters, and polyacetal polymers described in JP-A-2013-253227. The amount of the (G) plasticizer to be added is preferably 5% by mass to 500% by mass with respect to 100 parts of the (A) resin. If the amount is within this range, the pattern filling and averaging will be excellent.
[0102] The thickness of the adhesive film-forming material used in the present invention may be appropriately selected, but is preferably 2 to 100 nm, and more preferably 5 to 20 nm.
[0103] Furthermore, the adhesion film forming material of the present invention is extremely useful as an adhesion film material for multi-layer resist processes such as a two-layer resist process or a four-layer resist process using a resist underlayer film and a silicon-containing intermediate film.
[0104] The silicon-containing intermediate film can be a silicon-containing resist intermediate film or an inorganic hard mask intermediate film according to the pattern forming method described later. The inorganic hard mask intermediate film is preferably selected from a silicon oxide film, a silicon nitride film, and a silicon oxynitride film.
[0105] [Method of forming adhesive film] The present invention provides a method for forming an adhesion film that has high adhesion to an overlying resist film and has an effect of preventing collapse of a fine pattern in a fine patterning process using a multilayer resist method in a semiconductor device manufacturing process, using the above-mentioned adhesion film forming material.
[0106] In the method for forming an adhesive film of the present invention, the adhesive film forming material is coated on a substrate to be processed by spin coating or the like. After spin coating, the organic solvent is evaporated, and baking (heat treatment) is performed to promote a crosslinking reaction in order to prevent intermixing with the resist upper layer film or the silicon-containing intermediate film. Baking is preferably performed at 100°C or higher and 300°C or lower for 10 to 600 seconds, more preferably at 200°C or higher and 250°C or lower for 10 to 300 seconds. Considering the damage to the adhesive film and the influence on the deformation of the wafer, the upper limit of the heating temperature in the wafer process of lithography is preferably 300°C or lower, more preferably 250°C or lower.
[0107] That is, the present invention provides a method for forming an adhesion film that functions as an adhesion layer used in the manufacturing process of a semiconductor device, which comprises spin-coating the adhesion film-forming material described above onto a substrate to be processed, and heat-treating the substrate coated with the adhesion film-forming material at a temperature of 100°C or higher and 300°C or lower for 10 to 600 seconds to form a hardened film.
[0108] In addition, in the method for forming an adhesion film of the present invention, the adhesion film forming material of the present invention is coated on a substrate to be processed by the spin coating method or the like as described above, and the adhesion film forming material is baked in an atmosphere with an oxygen concentration of 0.1% to 21% to harden the adhesion film, thereby forming the adhesion film. By baking the adhesion film forming material of the present invention in such an oxygen atmosphere, a sufficiently hardened film can be obtained.
[0109] That is, the present invention provides a method for forming an adhesion film that functions as an adhesion layer used in the manufacturing process of a semiconductor device, which comprises spin-coating the adhesion film-forming material described above onto a substrate to be processed, and heat-treating the substrate coated with the adhesion film-forming material in an atmosphere with an oxygen concentration of 0.1% or more and 21% or less to form a hardened film.
[0110] The atmosphere during baking may be air or may contain an inert gas such as N2, Ar, or He. In this case, the atmosphere may have an oxygen concentration of less than 0.1%. The baking temperature and the like may be the same as above. Even if the substrate to be processed contains a material that is unstable when heated in an oxygen atmosphere, the crosslinking reaction during the formation of the adhesive film can be promoted without causing deterioration of the substrate to be processed.
[0111] That is, the present invention provides a method for forming an adhesion film that functions as an adhesion layer used in the manufacturing process of a semiconductor device, which comprises spin-coating the adhesion film-forming material described above onto a substrate to be processed, and heat-treating the substrate coated with the adhesion film-forming material in an atmosphere with an oxygen concentration of less than 0.1%, thereby forming a hardened film.
[0112] [Pattern formation method] In the present invention, there is provided a method for forming a pattern on a workpiece substrate, comprising the steps of: (I-1) A step of applying the above-described adhesive film-forming material onto a substrate to be processed, followed by heat treatment to form an adhesive film; (I-2) forming a resist top layer film on the adhesion film using a photoresist material; (I-3) a step of forming a circuit pattern on the resist upper layer film by pattern-exposing the resist upper layer film and then developing the resist upper layer film with a developer; (I-4) a step of transferring the pattern to the adhesive film by dry etching using the resist upper layer film on which the circuit pattern is formed as a mask; and (I-5) a step of processing the substrate to be processed using the adhesive film to which the pattern has been transferred as a mask to form a pattern on the substrate to be processed; The present invention provides a pattern forming method comprising the steps of:
[0113] The pattern forming method of the present invention will be described below taking a four-layer resist process as an example, but is not limited to this process. First, a method for forming a pattern on a substrate to be processed is provided, which comprises at least forming a resist underlayer film on the substrate to be processed using an organic film material, forming a silicon-containing intermediate film (silicon-containing resist intermediate film) on the resist underlayer film using a resist intermediate film material containing silicon atoms, forming an adhesion film on the silicon-containing resist intermediate film using the adhesion film-forming material of the present invention, forming a resist upperlayer film on the adhesion film using a resist upperlayer film material consisting of a photoresist composition to form a multi-layer resist film, exposing a pattern circuit region of the resist upperlayer film, and then developing with a developer to form a resist upperlayer film pattern on the resist upperlayer film, etching the adhesion film using the obtained resist upperlayer film pattern as an etching mask to form an adhesion film pattern, etching the silicon-containing resist intermediate film using the obtained adhesion film pattern as an etching mask to form a silicon-containing resist intermediate film pattern, etching the resist underlayer film using the obtained silicon-containing resist intermediate film pattern as an etching mask to form a resist underlayer film pattern, and further etching the substrate to be processed using the obtained resist underlayer film pattern as an etching mask to form a pattern on the substrate to be processed.
[0114] That is, a method for forming a pattern on a substrate to be processed, comprising the steps of: (II-1) forming a resist underlayer film on a substrate to be processed; (II-2) forming a silicon-containing resist intermediate film on the resist underlayer film; (II-3) a step of applying the above-described adhesion film-forming material onto the silicon-containing resist intermediate film, followed by heat treatment to form an adhesion film; (II-4) forming a resist top layer film on the adhesion film using a photoresist material; (II-5) a step of forming a circuit pattern on the resist upper layer film by pattern-exposing the resist upper layer film and then developing the resist upper layer film with a developer; (II-6) a step of transferring the pattern to the adhesive film by dry etching using the resist upper layer film on which the circuit pattern is formed as a mask; (II-7) a step of transferring the pattern to the silicon-containing resist intermediate film by dry etching using the adhesion film on which the pattern is formed as a mask; (II-8) a step of transferring a pattern to the resist underlayer film by dry etching using the silicon-containing resist intermediate film to which the pattern has been transferred as a mask; and (II-9) a step of processing the substrate using the resist underlayer film to which the pattern has been transferred as a mask to form a pattern on the substrate; The present invention provides a pattern forming method comprising the steps of:
[0115] As the silicon-containing resist intermediate film in the four-layer resist process, a polysilsesquioxane-based intermediate film is also preferably used. By imparting an anti-reflection effect to the silicon-containing resist intermediate film, reflection can be suppressed. In particular, for 193 nm exposure, if a material containing many aromatic groups and having high substrate etching resistance is used as the resist underlayer film, the k value becomes high and the substrate reflection becomes high, but by suppressing reflection with the silicon-containing resist intermediate film, the substrate reflection can be reduced to 0.5% or less. As the silicon-containing resist intermediate film having an anti-reflection effect, anthracene is preferably used for 248 nm and 157 nm exposure, and polysilsesquioxane is preferably used for 193 nm exposure, which is pendant with a light-absorbing group having a phenyl group or a silicon-silicon bond and crosslinked with acid or heat.
[0116] In this case, the formation of the silicon-containing resist intermediate film by spin coating is easier and more cost-effective than the CVD method.
[0117] In addition, an inorganic hard mask intermediate film may be formed as the silicon-containing intermediate film. In this case, at least a resist underlayer film is formed on a substrate to be processed using an organic film material, an inorganic hard mask intermediate film selected from a silicon oxide film, a silicon nitride film, and a silicon oxynitride film is formed on the resist underlayer film, an adhesion film is formed on the inorganic hard mask intermediate film using the adhesion film forming material of the present invention, a resist upper layer film is formed on the adhesion film using a resist upper layer film material consisting of a photoresist composition, and a pattern circuit region of the resist upper layer film is exposed, and then developed with a developer to form a resist upper layer film pattern on the resist upper layer film, the adhesion film is etched using the obtained resist upper layer film pattern as an etching mask to form an adhesion film pattern, the inorganic hard mask intermediate film is etched using the obtained adhesion film pattern as an etching mask to form an inorganic hard mask intermediate film pattern, the resist underlayer film is etched using the obtained inorganic hard mask intermediate film pattern as an etching mask to form a resist underlayer film pattern, and further, the substrate to be processed is etched using the obtained resist underlayer film pattern as an etching mask to form a pattern on the substrate to be processed.
[0118] That is, a method for forming a pattern on a substrate to be processed, comprising the steps of: (III-1) forming a resist underlayer film on a substrate to be processed; (III-2) forming an inorganic hard mask intermediate film selected from a silicon oxide film, a silicon nitride film, and a silicon oxynitride film on the resist underlayer film; (III-3) A step of forming an adhesion film by applying the above-described adhesion film forming material onto the inorganic hard mask intermediate film and then performing a heat treatment; (III-4) forming a resist top layer film on the adhesion film using a photoresist material; (III-5) a step of forming a circuit pattern on the resist upper layer film by pattern-exposing the resist upper layer film and then developing the resist upper layer film with a developer; (III-6) a step of transferring the pattern to the adhesive film by dry etching using the resist upper layer film on which the circuit pattern has been formed as a mask; (III-7) a step of transferring the pattern to the inorganic hard mask intermediate film by dry etching using the adhesive film on which the pattern is formed as a mask; (III-8) a step of transferring a pattern to the resist underlayer film by dry etching using the inorganic hard mask intermediate film to which the pattern has been transferred as a mask; and (III-9) a step of processing the substrate using the resist underlayer film to which the pattern has been transferred as a mask to form a pattern on the substrate; The present invention provides a pattern forming method comprising the steps of:
[0119] As described above, when forming an inorganic hard mask intermediate film on a resist underlayer film, a silicon oxide film, a silicon nitride film, and a silicon oxide nitride film (SiON film) can be formed by a CVD method, an ALD method, or the like. In particular, it is preferable to form the inorganic hard mask intermediate film by a CVD method or an ALD method. For example, a method for forming a silicon nitride film is described in JP-A-2002-334869 and WO-A-2004 / 066377. The thickness of the inorganic hard mask intermediate film is preferably 5 to 200 nm, more preferably 10 to 100 nm. In addition, as the inorganic hard mask intermediate film, a SiON film, which has a high effect as an anti-reflection film, is most preferably used. Since the substrate temperature during the formation of the SiON film is 300 to 500°C, the resist underlayer film needs to withstand a temperature of 300 to 500°C.
[0120] The resist top layer film in the four-layer resist process may be either positive or negative, and may be the same as a photoresist composition that is commonly used, but is more preferably formed using a negative resist composition.The resist top layer film is preferably formed using a resist top layer film material that contains at least an organometallic compound and a solvent, and the organometallic compound is preferably selected from the group consisting of titanium, cobalt, copper, zinc, zirconium, lead, indium, tin, antimony, and hafniumIt is more preferable that the composition contains at least one selected from the group consisting of: After spin-coating the photoresist composition, pre-baking is performed, preferably at 60 to 180° C. for 10 to 300 seconds. Thereafter, exposure is performed according to a conventional method, followed by post-exposure baking (PEB) and development to obtain a resist upper layer film pattern. The thickness of the resist upper layer film is not particularly limited, but is preferably 30 to 500 nm, and more preferably 50 to 400 nm.
[0121] A circuit pattern (resist upper layer film pattern) is formed on the resist upper layer film. In forming the circuit pattern, it is preferable to form the circuit pattern by photolithography with a wavelength of 10 nm or more and 300 nm or less, direct drawing with an electron beam, nanoimprinting, or a combination of these.
[0122] Examples of the exposure light include high-energy rays with a wavelength of 300 nm or less, specifically far ultraviolet rays, KrF excimer laser light (248 nm), ArF excimer laser light (193 nm), F2 laser light (157 nm), Kr2 laser light (146 nm), Ar2 laser light (126 nm), soft X-rays (EUV) of 3 to 20 nm, electron beams (EB), ion beams, X-rays, and the like.
[0123] In forming the circuit pattern, it is preferable to develop the circuit pattern using an alkali development method or an organic solvent development method.
[0124] Next, etching is performed using the resist top layer film pattern as a mask. In the four-layer resist process, the adhesion film is etched using an oxygen-based gas with the resist top layer film pattern as a mask. This forms an adhesion film pattern.
[0125] Next, etching is performed using the obtained adhesive film pattern as a mask. The etching of the silicon-containing resist intermediate film or the inorganic hard mask intermediate film is performed using the adhesive film pattern as a mask with a fluorocarbon-based gas. In this way, a silicon-containing resist intermediate film pattern or an inorganic hard mask intermediate film pattern is formed.
[0126] The etching of the adhesion film may be carried out prior to and consecutively with the etching of the silicon-containing intermediate film, or the etching of the silicon-containing intermediate film may be carried out after etching only the adhesion film, for example by changing the etching apparatus.
[0127] Next, the resist underlayer film is etched using the obtained silicon-containing resist intermediate film pattern or inorganic hard mask intermediate film pattern as a mask.
[0128] The next step, etching of the substrate to be processed, can also be done by standard methods; for example, if the substrate to be processed is a SiO2, SiN, or silica-based low dielectric constant insulating film, etching is done mainly with fluorocarbon gases, and for p-Si, Al, or W, etching is done mainly with chlorine- or bromine-based gases. When etching the substrate with fluorocarbon gases, the silicon-containing intermediate film pattern in the three-layer resist process is peeled off at the same time as the substrate is processed. When etching the substrate with chlorine- or bromine-based gases, the silicon-containing intermediate film pattern must be peeled off by separate dry etching with fluorocarbon gases after substrate processing.
[0129] The substrate to be processed is not particularly limited, and may be a semiconductor device substrate, or a semiconductor device substrate having a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal oxide carbide film, or a metal oxide nitride film formed thereon. As the metal, silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum, or an alloy thereof may be used.
[0130] Specifically, substrates such as Si, α-Si, p-Si, SiO2, SiN, SiON, W, TiN, Al, etc., and substrates on which a layer to be processed is formed, etc. are used. As the layer to be processed, various low-k films such as Si, SiO2, SiON, SiN, p-Si, α-Si, W, W-Si, Al, Cu, Al-Si, etc. and their stopper films are used, and can be formed to a thickness of usually 50 to 10,000 nm, particularly 100 to 5,000 nm. When forming a layer to be processed, the substrate and the layer to be processed are made of different materials.
[0131] An example of a four-layer resist process is specifically shown below with reference to Fig. 1. In the four-layer resist process, as shown in Fig. 1(A), a resist underlayer film 3 is formed using an organic film material on a processable layer 2 laminated on a substrate 1, and then a silicon-containing intermediate film 4 is formed thereon, an adhesion film 5 is formed thereon using the adhesion film-forming material of the present invention, and a resist upper layer film 6 is formed thereon.
[0132] Next, as shown in FIG. 1(B), the exposed portion 7 of the resist upper layer film is exposed, and PEB and development are performed to form a resist pattern 6a (FIG. 1(C)). Using the obtained resist pattern 6a as a mask, the adhesion film 5 is etched using an O2-based gas to form an adhesion film pattern 5a. (FIG. 1(D)). Using the obtained adhesion film pattern 5a as a mask, the silicon-containing intermediate film 4 is etched using a CF2-based gas to form a silicon-containing intermediate film pattern 4a (FIG. 1(E)). After removing the adhesion film pattern 5a, using the obtained silicon-containing intermediate film pattern 4a as a mask, the resist underlayer film 3 is etched using an O2-based gas to form a resist underlayer film pattern 3a (FIG. 1(F)). Furthermore, after removing the silicon-containing intermediate film pattern 4a, the processed layer 2 is etched using the resist underlayer film pattern 3a as a mask to form a pattern 2a (FIG. 1(G)).
[0133] As described above, the pattern forming method of the present invention makes it possible to form a fine pattern on a substrate to be processed with high precision in a multi-layer resist process. EXAMPLES
[0134] The present invention will be described in more detail below with reference to Synthesis Examples, Comparative Synthesis Examples, Examples, and Comparative Examples, but the present invention is not limited thereto. The molecular weight was measured by gel permeation chromatography (GPC) using tetrahydrofuran (THF) or N,N-dimethylformamide (DMF) as an eluent, and the polydispersity (Mw / Mn) was calculated from the weight average molecular weight (Mw) and number average molecular weight (Mn) in terms of polystyrene.
[0135] The polymers (A1) to (A15) and the comparative polymers (R1) to (R5) used as the resin (A) for the adhesive film-forming material were synthesized using the monomers (B1) to (B9) shown below. [ka]
[0136] [Synthesis Example 1] Synthesis of polymer (A1) In a nitrogen atmosphere, 45.1 g of monomer (B1), 34.8 g of monomer (B5), 20.0 g of monomer (B6), 4.70 g of V-601 (2,2'-azobis(isobutyric acid) dimethyl, manufactured by Wako Pure Chemical Industries, Ltd.), 1.28 g of SEA (2-mercaptoethanol, manufactured by Tokyo Chemical Industry Co., Ltd.), and 340 g of DAA (diacetone alcohol) were weighed in a 1 L flask, and the mixture was degassed while stirring to prepare a monomer-polymerization initiator solution. In another 1 L flask in a nitrogen atmosphere, 60 g of DAA was weighed, and the mixture was degassed while stirring, and then heated until the internal temperature reached 80°C. The monomer-polymerization initiator solution was added dropwise over 4 hours, and the temperature of the polymerization liquid was kept at 80°C while stirring for 16 hours, and then cooled to room temperature. The obtained polymerization liquid was added dropwise to 1,500 g of vigorously stirred hexane, and the precipitated polymer was filtered off. The polymer was washed twice with 600 g of hexane and then vacuum dried at 50° C. for 20 hours to obtain a white powdery polymer (A1) (yield: 101.5 g, 96%). The weight average molecular weight (Mw) and dispersity (Mw / Mn) of the polymer (A1) were determined by GPC to be Mw=15,300 and Mw / Mn=1.98.
[0137] [ka]
[0138] [Synthesis Example 2] Synthesis of polymer (A2) In a nitrogen atmosphere, 45.1 g of monomer (B1), 34.8 g of monomer (B5), 20.0 g of monomer (B6), 4.70 g of V-601, and 340 g of DAA were weighed in a 1 L flask, and the mixture was degassed while stirring to prepare a monomer-polymerization initiator solution. 60 g of DAA was weighed in another 1 L flask in a nitrogen atmosphere, and the mixture was degassed while stirring, and then heated until the internal temperature reached 80°C. The monomer-polymerization initiator solution was added dropwise over 4 hours, and the temperature of the polymerization liquid was kept at 80°C while stirring for 16 hours, and then cooled to room temperature. The obtained polymerization liquid was added dropwise to 1,500 g of hexane that was vigorously stirred, and the precipitated polymer was filtered off. Furthermore, the obtained polymer was washed twice with 600 g of hexane, and then vacuum dried at 50°C for 20 hours to obtain a white powdery polymer (A2) (yield 102.8 g, yield 98%). The weight average molecular weight (Mw) and the dispersity (Mw / Mn) of the polymer (A2) were determined by GPC, and were found to be Mw=29,300 and Mw / Mn=2.20.
[0139] [ka]
[0140] [Synthesis Example 3] Synthesis of polymer (A3) In a nitrogen atmosphere, 45.1 g of monomer (B1), 34.8 g of monomer (B5), 20.0 g of monomer (B6), 0.94 g of V-601, and 340 g of DAA were weighed in a 1 L flask, and the mixture was degassed while stirring to prepare a monomer-polymerization initiator solution. 60 g of DAA was weighed in another 1 L flask in a nitrogen atmosphere, and the mixture was degassed while stirring, and then heated until the internal temperature reached 80°C. The monomer-polymerization initiator solution was added dropwise over 4 hours, and the temperature of the polymerization liquid was kept at 80°C while stirring for 16 hours, and then cooled to room temperature. The obtained polymerization liquid was added dropwise to 1,500 g of hexane that was vigorously stirred, and the precipitated polymer was filtered off. Furthermore, the obtained polymer was washed twice with 600 g of hexane, and then vacuum dried at 50°C for 20 hours to obtain a white powdery polymer (A3) (yield 99.3 g, yield 98%). The weight average molecular weight (Mw) and the dispersity (Mw / Mn) of the polymer (A3) were determined by GPC, and were found to be Mw=52,500 and Mw / Mn=2.29.
[0141] [ka]
[0142] [Synthesis Examples 4 to 15] Synthesis of Polymers (A4) to (A15) Except for using the monomers and polymerization initiators shown in Table 1, the reaction and post-treatment were carried out under the same conditions as in Synthesis Examples 1 to 3, and polymers (A4) to (A15) were obtained as products. The weight average molecular weight (Mw) and dispersity (Mw / Mn) determined by GPC were In Table 1 show.
[0143] [Table 1]
[0144] [Comparative Synthesis Example 1] Synthesis of Comparative Polymer (R1) In a nitrogen atmosphere, 100.0 g of monomer (B5), 1.62 g of V-601, and PGMEA (propylene glycol monomethyl ether) were added to a 1 L flask. etherAfter weighing 340 g of dimethylaminopropanediol (acetate), the mixture was degassed while stirring to prepare a monomer-polymerization initiator solution. 60 g of PGMEA was weighed in a separate 1 L flask with a nitrogen atmosphere, and the mixture was degassed while stirring, and then heated until the internal temperature reached 80°C. The monomer-polymerization initiator solution was added dropwise over 4 hours, and the temperature of the polymerization liquid was kept at 80°C while stirring for 16 hours, and then cooled to room temperature. The obtained polymerization liquid was added dropwise to 1,500 g of vigorously stirred hexane, and the precipitated polymer was separated by filtration. Furthermore, the obtained polymer was washed twice with 600 g of hexane, and then vacuum dried at 50°C for 20 hours to obtain a white powdery polymer (R1) (yield 98.2 g, yield 97%). The weight average molecular weight (Mw) and dispersity (Mw / Mn) of the polymer (R1) were determined by GPC to be Mw=30,300 and Mw / Mn=1.51.
[0145] [ka]
[0146] [Comparative Synthesis Example 2] Synthesis of Comparative Polymer (R2) In a nitrogen atmosphere, 62.8 g of monomer (B5), 37.2 g of monomer (B6), 1.45 g of V-601, and 340 g of PGMEA were weighed in a 1 L flask, and the mixture was degassed while stirring to prepare a monomer-polymerization initiator solution. 60 g of PGMEA was weighed in another 1 L flask in a nitrogen atmosphere, and the mixture was degassed while stirring, and then heated until the internal temperature reached 80°C. The monomer-polymerization initiator solution was added dropwise over 4 hours, and the temperature of the polymerization liquid was kept at 80°C while stirring for 16 hours, and then cooled to room temperature. The obtained polymerization liquid was added dropwise to 1,500 g of hexane that was vigorously stirred, and the precipitated polymer was filtered off. Furthermore, the obtained polymer was washed twice with 600 g of hexane, and then vacuum dried at 50°C for 20 hours to obtain a white powdery polymer (R2) (yield 97.5 g, yield 96%). The weight average molecular weight (Mw) and the polydispersity (Mw / Mn) of the polymer (R2) were determined by GPC, and were found to be Mw=33,500 and Mw / Mn=1.88.
[0147] [ka]
[0148] [Comparative Synthesis Example 3] Synthesis of Comparative Polymer (R3) In a nitrogen atmosphere, 64.3 g of monomer (B5), 35.7 g of monomer (B7), 1.49 g of V-601, and 340 g of PGMEA were weighed in a 1 L flask, and the mixture was degassed while stirring to prepare a monomer-polymerization initiator solution. 60 g of PGMEA was weighed in another 1 L flask in a nitrogen atmosphere, and the mixture was degassed while stirring, and then heated until the internal temperature reached 80°C. The monomer-polymerization initiator solution was added dropwise over 4 hours, and the temperature of the polymerization liquid was kept at 80°C while stirring for 16 hours, and then cooled to room temperature. The obtained polymerization liquid was added dropwise to 1,500 g of hexane that was vigorously stirred, and the precipitated polymer was filtered off. Furthermore, the obtained polymer was washed twice with 600 g of hexane, and then vacuum dried at 50°C for 20 hours to obtain a white powdery polymer (R3) (yield 96.5 g, yield 95%). The weight average molecular weight (Mw) and the polydispersity (Mw / Mn) of the polymer (R3) were determined by GPC, and were found to be Mw=32,200 and Mw / Mn=1.80.
[0149] [ka]
[0150] [Comparative Synthesis Example 4] Synthesis of Comparative Polymer (R4) In a nitrogen atmosphere, 66.1 g of monomer (B5), 33.9 g of monomer (B8), 1.49 g of V-601, and 340 g of PGMEA were weighed in a 1 L flask, and the mixture was degassed while stirring to prepare a monomer-polymerization initiator solution. 60 g of PGMEA was weighed in another 1 L flask in a nitrogen atmosphere, and the mixture was degassed while stirring, and then heated until the internal temperature reached 80°C. The monomer-polymerization initiator solution was added dropwise over 4 hours, and the temperature of the polymerization liquid was kept at 80°C while stirring for 16 hours, and then cooled to room temperature. The obtained polymerization liquid was added dropwise to 1,500 g of hexane that was vigorously stirred, and the precipitated polymer was filtered off. Furthermore, the obtained polymer was washed twice with 600 g of hexane, and then vacuum dried at 50°C for 20 hours to obtain a white powdery polymer (R4) (yield 97.0 g, yield 96%). The weight average molecular weight (Mw) and the polydispersity (Mw / Mn) of the polymer (R4) were determined by GPC, and were found to be Mw=31,200 and Mw / Mn=1.82.
[0151] [ka]
[0152] [Comparative Synthesis Example 5] Synthesis of Comparative Polymer (R5) In a nitrogen atmosphere, 100.0 g of monomer (B9), 2.21 g of V-601, and 340 g of PGMEA were weighed in a 1 L flask, and the mixture was degassed while stirring to prepare a monomer-polymerization initiator solution. 60 g of PGMEA was weighed in another 1 L flask in a nitrogen atmosphere, and the mixture was degassed while stirring, and then heated until the internal temperature reached 80°C. The monomer-polymerization initiator solution was added dropwise over 4 hours, and the temperature of the polymerization liquid was kept at 80°C while stirring for 16 hours, and then cooled to room temperature. The obtained polymerization liquid was added dropwise to 1,500 g of hexane that was vigorously stirred, and the precipitated polymer was filtered off. Furthermore, the obtained polymer was washed twice with 600 g of hexane, and then vacuum dried at 50°C for 20 hours to obtain a white powdery polymer (R5) (yield 95.2 g, yield 93%). The weight average molecular weight (Mw) and the dispersity (Mw / Mn) of the polymer (R5) were determined by GPC, and were found to be Mw=33,200 and Mw / Mn=1.95.
[0153] [ka]
[0154] Preparation of adhesive film forming materials (AL-1 to 27, comparative AL-1 to 13) The adhesive film-forming materials were prepared using the polymers (A1) to (A15) and comparative polymers (R1) to (R5), the thermal acid generators (AG1) to (AG4), the photoacid generator (AG5), and the crosslinkers (X1) to (X3). The materials were dissolved in an organic solvent containing 0.1% by mass of PF636 (manufactured by OMNOVA) in the proportions shown in Table 2, and then filtered through a 0.1 μm fluororesin filter to prepare the adhesive film-forming materials (AL-1 to 27, comparative AL-1 to 13).
[0155] [ka]
[0156] [Table 2]
[0157] The compositions in Table 2 are as follows. Organic solvent: PGMEA (propylene glycol monomethyl ether ether acetate) CyH (Cyclohexanone) DAA (Diacetone Alcohol) EL (Ethyl lactate) GBL (γ-butyrolactone)
[0158] Example 1 Solvent Resistance Evaluation (Examples 1-1 to 1-27, Comparative Examples 1-1 to 1-13) The adhesive film forming materials (AL-1 to 27, Comparative AL-1 to 13) prepared above were applied onto a silicon substrate, baked at 215°C for 60 seconds, the film thickness was measured, PGMEA solvent was dispensed onto it, left for 30 seconds, spin-dried, baked at 100°C for 60 seconds to evaporate the PGMEA solvent, the film thickness was measured again, and the difference in film thickness before and after PGMEA treatment was calculated to evaluate the solvent resistance. The results are shown in Table 3.
[0159] [Table 3]
[0160] As shown in Table 3, in Examples 1-1 to 1-27 and Comparative Examples 1-5 to 1-13 using the adhesion film-forming material of the present invention (AL-1 to 27), the film thickness hardly decreased by the solvent treatment and the film had good solvent resistance. On the other hand, in Comparative Examples 1-1 to 1-4 not containing the thermal acid generator and the crosslinking agent, sufficient solvent resistance was not ensured.
[0161] Example 2 Adhesion Test (Examples 2-1 to 2-27, Comparative Examples 2-1 to 2-9) The above adhesive film forming materials (AL-1 to 27, comparative AL-5 to 13) were applied onto a SiO2 wafer substrate and baked for 60 seconds at 215°C in air using a hot plate to form an adhesive film with a thickness of 5 nm (AL-1 to 19, comparative AL-5 to 11, 13) or 20 nm (AL-20 to 27, comparative AL-12). The wafer with the adhesive film was cut into a 1 x 1 cm square, and an aluminum pin with epoxy adhesive was attached to the cut wafer using a special jig. The aluminum pin was then attached to the substrate by heating at 150°C for 1 hour in an oven. After cooling to room temperature, the initial adhesion was evaluated by resistance using a thin film adhesion strength measuring device (Sebastian Five-A).
[0162] An explanatory diagram of the adhesion measurement method is shown in Figure 2. In Figure 2, 8 is the silicon wafer (substrate), 9 is the cured film, 10 is the aluminum pin with adhesive, 11 is the support base, 12 is the grip, and 13 indicates the tensile direction. The adhesion strength is the average value of 12 measurements, and the higher the value, the stronger the adhesion of the adhesive film to the substrate. The adhesion was evaluated by comparing the obtained values. The results are shown in Table 4.
[0163] [Table 4]
[0164] As shown in Table 4, it was confirmed that Examples 2-1 to 2-27, which used the adhesive film-forming material of the present invention (AL-1 to 27), had excellent adhesion. It was also found that Comparative Examples 2-1 to 2-8, which used a polymer containing a structural unit represented by general formula (2), also had good adhesion. On the other hand, Comparative Example 2-9, which used a polymer not containing a structural unit represented by general formula (2), had inferior adhesion compared to the other examples.
[0165] Example 3 ArF immersion exposure pattern formation test using positive resist (Examples 3-1 to 3-27, Comparative Examples 3-1 to 3-8) On a silicon wafer substrate, spin-on carbon ODL-301 (carbon content 88% by mass) manufactured by Shin-Etsu Chemical Co., Ltd. was applied and baked at 350°C for 60 seconds to form a resist underlayer film with a thickness of 200 nm. A CVD-SiON hard mask intermediate film was formed thereon, and the above-mentioned adhesion film forming material (AL1-27, comparative AL5-12) was further applied and baked at 215°C for 60 seconds to form an adhesion film with a thickness of 5 nm (AL-1-19, comparative AL-5-11) or 20 nm (AL-20-27, comparative AL-12), and a positive resist upper layer film material described in Table 5 was applied thereon and baked at 105°C for 60 seconds to form a resist upper layer film with a thickness of 100 nm. An immersion protective film material (TC-1) was applied on the resist upper layer film and baked at 90°C for 60 seconds to form a protective film with a thickness of 50 nm.
[0166] A positive resist top layer film material (ArF single layer resist) was prepared by dissolving a polymer (PRP-A1), an acid generator (PAG1), and a basic compound (Amine1) in a solvent containing 0.1 mass% FC-430 (Sumitomo 3M Limited) in the proportions shown in Table 5, and filtering the solution through a 0.1 μm fluororesin filter.
[0167] [Table 5]
[0168] Resist polymer: PRP-A1 Molecular weight (Mw)=8,600 Dispersity (Mw / Mn)=1.88 [ka]
[0169] Acid generator: PAG1 [ka]
[0170] Basic compound: Amine1 [ka]
[0171] The immersion protective film material (TC-1) was prepared by dissolving the protective film polymer (PP1) in an organic solvent in the ratio shown in Table 6, and filtering the solution through a 0.1 μm fluorine resin filter.
[0172] [Table 6]
[0173] Protective film polymer: PP1 Molecular weight (Mw)=8,800 Dispersity (Mw / Mn)=1.69 [ka]
[0174] Next, the sample was exposed to light using an ArF immersion exposure system (Nikon Corporation; NSR-S610C, NA 1.30, σ 0.98 / 0.65, 35-degree dipole s-polarized illumination, 6% halftone phase shift mask), baked at 100°C for 60 seconds (PEB), and developed with a 2.38% by mass tetramethylammonium hydroxide (TMAH) aqueous solution for 30 seconds to obtain a 40 nm 1:1 line and space pattern. The cross-sectional shape and roughness of this pattern were observed using an electron microscope. In addition, the minimum dimension at which the lines could be resolved without collapsing when the line dimensions were narrowed by increasing the exposure dose was determined, and this was taken as the collapse limit (nm). The smaller the value, the higher the collapse resistance, which is preferable.
[0175] The cross-sectional shape of the obtained pattern was evaluated using an electron microscope (S-4700) manufactured by Hitachi, Ltd., and the pattern roughness was evaluated using an electron microscope (CG4000) manufactured by Hitachi High-Technologies Corp. The results are shown in Table 7.
[0176] [Table 7]
[0177] As shown in Table 7, Examples 3-1 to 3-27 using the adhesion film-forming material of the present invention (AL-1 to 27) show superior collapse suppression performance compared to the comparative examples, and the pattern shape is also vertical. On the other hand, Comparative Examples 3-1 to 3-8 not including the resin contained in the adhesion film-forming material of the present invention also show high adhesion and excellent collapse suppression performance, but the pattern has a skirted or inverse tapered shape, and it can be seen that Examples 3-1 to 3-27 using the adhesion film-forming material of the present invention are superior in pattern formation ability. It can be seen that Comparative Example 3-4, which does not have a photoacid generating site in the polymer but has a separate photoacid generator (AG5), shows that the pattern has an inverse tapered shape and the pattern roughness is deteriorated.
[0178] Example 4 ArF immersion exposure pattern formation test using negative resist (Examples 4-1 to 4-27, Comparative Examples 4-1 to 4-8) As in the patterning test using the positive resist described above, an organic underlayer film and a CVD-SiON hard mask intermediate film were formed on a silicon wafer, and an adhesion film was further formed on top of that. A single layer resist for ArF made of the negative resist upper layer film material listed in Table 8 was applied on top of that, and baked at 100°C for 60 seconds to form a photoresist layer with a thickness of 100 nm. An immersion protective film (TC-1) was applied on the photoresist film and baked at 90°C for 60 seconds to form a protective film with a thickness of 50 nm.
[0179] The negative resist top layer film material was prepared by dissolving the aforementioned polymer (PRP-A1), acid generator (PAG1), and basic compound (Amine1) in a solvent containing 0.1 mass% FC-430 (manufactured by Sumitomo 3M Limited) in the proportions shown in Table 8, and filtering through a 0.1 μm fluororesin filter.
[0180] [Table 8]
[0181] Next, the sample was exposed to light using an ArF immersion exposure apparatus (Nikon Corporation; NSR-S610C, NA 1.30, σ 0.98 / 0.65, 35-degree dipole s-polarized illumination, 6% halftone phase shift mask), baked at 100°C for 60 seconds (PEB), and while rotating at 30 rpm, butyl acetate was ejected from the development nozzle as a developer for 3 seconds. Then, the rotation was stopped and paddle development was performed for 27 seconds, and the sample was rinsed with diisoamyl ether and spin-dried, and baked at 100°C for 20 seconds to evaporate the rinse solvent. This patterning resulted in a negative line and space pattern of 43 nm. The cross-sectional shape of this pattern was observed using an electron microscope. In addition, the minimum dimension at which the lines could be resolved without collapsing when the line dimensions were narrowed by reducing the exposure dose was determined, and this was taken as the collapse limit (nm). The smaller the value, the higher the collapse resistance, which is preferable.
[0182] The cross-sectional shape of the obtained pattern was evaluated using an electron microscope (S-4700) manufactured by Hitachi, Ltd., and the pattern collapse after development was evaluated using an electron microscope (CG4000) manufactured by Hitachi High-Technologies Corp. The results are shown in Table 9.
[0183] [Table 9]
[0184] As shown in Table 9, in the pattern formation test using a negative resist, a vertical pattern was obtained in all examples. In Examples 4-1 to 4-27 using the adhesion film-forming material of the present invention (AL-1 to 27), the collapse limit value is smaller than when a positive resist is used, and it is understood that the negative resist has better adhesion. On the other hand, Comparative Examples 4-1 to 4-8, which do not contain the resin contained in the adhesion film-forming material of the present invention, also have high adhesion and excellent collapse suppression performance, but it is understood that Examples 4-1 to 4-27, which used the adhesion film-forming material of the present invention, have a smaller collapse limit value and are more excellent in adhesion.
[0185] Example 5 Electron beam pattern formation test (Example 5-1, Comparative Example 5-1) The above-mentioned adhesion film forming material (AL-4, Comparative AL-5) was applied onto a silicon wafer substrate and baked at 215°C for 60 seconds to form an adhesion film with a thickness of 5 nm, and then a metal-containing resist composition of the resist upper layer film material was applied thereon and baked at 180°C for 60 seconds to form a resist upper layer film with a thickness of 60 nm.
[0186] The resist upper layer film material (metal-containing resist composition) was prepared by dissolving the titanium-containing compound (AM-1) and the metal salt sensitizer (S-1) in 4-methyl-2-pentanol (MIBC) containing 0.1 mass % of FC-4430 (Sumitomo 3M Limited) in the ratios shown in Table 10, and filtering through a 0.1 μm fluororesin filter.
[0187] [Table 10]
[0188] Synthesis of titanium-containing compound (AM-1) A solution of 27 g of deionized water and 500 g of IPA was dropped into a solution of 284 g of titanium tetraisopropoxide (Tokyo Chemical Industry Co., Ltd.) in 500 g of 2-propanol (IPA) over 2 hours at room temperature while stirring. 180 g of 2,4-dimethyl-2,4-octanediol was added to the obtained solution and stirred at room temperature for 30 minutes. After concentrating this solution at 30°C under reduced pressure, it was further heated to 60°C and continued to be heated under reduced pressure until no distillate was produced. When no distillate was observed, 1,200 g of 4-methyl-2-pentanol (MIBC) was added and heated at 40°C under reduced pressure until no IPA was produced, obtaining 1,000 g of MIBC solution of titanium-containing compound AM-1 (compound concentration 25% by mass). The molecular weight of this product in terms of polystyrene was measured and found to be Mw=1,200.
[0189] Metal salt sensitizer: S-1 [ka]
[0190] Next, writing was performed in a vacuum chamber at an accelerating voltage of 50 kV using a JBX-9000MV (manufactured by JEOL Ltd.) After writing, the wafer was immediately baked (PEB) at 200°C for 60 seconds, and paddle developed with butyl acetate for 20 seconds to obtain a negative pattern. The obtained resist pattern was evaluated as follows. The exposure dose at which a 100 nm line and space (LS) was resolved at 1:1 was taken as the sensitivity, and the minimum dimension at which the line could be resolved without collapsing at the exposure dose was determined as the collapse limit (nm). The smaller the value, the higher the collapse resistance, which is preferable. The results are shown in Table 11.
[0191] [Table 11]
[0192] As shown in Table 11, Example 5-1, which used the adhesion film-forming material of the present invention (AL-4), has a smaller collapse limit value than Comparative Example 5-1, which did not use the adhesion material of the present invention, and it is clear that the present invention has excellent adhesion even with metal-containing resists.
[0193] From the above, the adhesion film forming material of the present invention has high adhesion to the resist overlying film and has the effect of preventing the collapse of a fine pattern, and is therefore extremely useful as an adhesion film material for use in a multilayer resist method. Furthermore, the pattern forming method of the present invention using this material makes it possible to form a fine pattern on a substrate to be processed with high precision.
[0194] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention. [Explanation of symbols]
[0195] 1...substrate, 2...processed layer, 2a...pattern (pattern formed on the processed layer), 3...resist underlayer film, 3a...resist underlayer film pattern, 4...silicon-containing intermediate film, 4a...silicon-containing intermediate film pattern, 5...adhesive film, 5a...adhesive film pattern, 6: resist upper layer film; 6a: resist upper layer film pattern; 7: exposed portion; 8...silicon wafer; 9...hardened film; 10...aluminum pin with adhesive; 11...support base; 12...grip; 13...pulling direction.
Claims
1. The adhesion film-forming material is used for an adhesion film formed directly under a resist upper layer film, the adhesion film-forming material comprising: (A) a resin having at least one structural unit containing a fluorine-substituted organic sulfonyl anion structure, and having two or more structural units represented by the following general formula (2) in addition to the structural unit containing the fluorine-substituted organic sulfonyl anion structure; (B) a thermal acid generator; and (C) an organic solvent, wherein the fluorine-substituted organic sulfonyl anion structure is a structure represented by the following general formula (1): 【Chemistry 1】 (In the above general formula (2), R 6 is a hydrogen atom or a methyl group, R 7 is a group selected from the following formulas (2-1) to (2-3). 【Chemistry 2】 (In the above formula, the dashed lines represent bonds.) 【Chemistry 3】 (In the formula, R 1 is a hydrogen atom or a methyl group. R 2 is a single bond, -Z 21 -C(═O)-O-, -Z 21 -O-, or -Z 21 -O-C(═O)-, Z 21 is a saturated hydrocarbylene group having 1 to 12 carbon atoms and may contain a carbonyl group, an ester bond, or an ether bond. R 3 to R 5 are each independently a hydrocarbyl group having 1 to 21 carbon atoms which may contain a hetero atom. In addition, any two of R 3 , R 4 , and R 5 may be bonded to each other to form a ring together with the sulfur atom to which they are bonded. A 1 is a hydrogen atom or a trifluoromethyl group.)
2. The R in the general formula (1) 2 2. The adhesive film forming material according to claim 1, wherein the compound contains a divalent organic group having an alicyclic structure.
3. 3. The adhesion film forming material according to claim 1, wherein the organic solvent (C) is a mixture of one or more organic solvents having a boiling point of less than 150°C and one or more organic solvents having a boiling point of 150°C or more and less than 220°C.
4. 4. The adhesive film forming material according to claim 1, wherein the weight average molecular weight of the resin (A) is 5,000 to 70,000.
5. The adhesion film forming material according to any one of claims 1 to 4, further comprising at least one selected from the group consisting of (D) a photoacid generator, (E) a surfactant, (F) a crosslinking agent, and (G) a plasticizer.
6. 6. The adhesion film forming material according to claim 1, wherein the resist upper layer film is formed using a negative resist composition.
7. 7. The adhesion film forming material according to claim 1, wherein the resist upper layer film is formed using a resist upper layer film material containing at least an organometallic compound and a solvent.
8. 8. The adhesive film forming material according to claim 7, wherein the organometallic compound contains at least one selected from the group consisting of titanium, cobalt, copper, zinc, zirconium, lead, indium, tin, antimony and hafnium.
9. A method for forming a pattern on a workpiece substrate, comprising the steps of: (I-1) A step of forming an adhesion film by applying the adhesion film forming material according to any one of claims 1 to 8 onto a substrate to be processed and then heat-treating the applied material; (I-2) forming a resist top layer film on the adhesion film using a photoresist material; (I-3) a step of forming a circuit pattern on the resist upper layer film by pattern-exposing the resist upper layer film and then developing the resist upper layer film with a developer; (I-4) a step of transferring the pattern to the adhesive film by dry etching using the resist upper layer film on which the circuit pattern is formed as a mask; and (I-5) a step of processing the substrate using the adhesive film to which the pattern has been transferred as a mask to form a pattern on the substrate; A pattern forming method comprising the steps of:
10. A method for forming a pattern on a workpiece substrate, comprising the steps of: (II-1) forming a resist underlayer film on a substrate to be processed; (II-2) forming a silicon-containing resist intermediate film on the resist underlayer film; (II-3) A step of forming an adhesion film by applying the adhesion film-forming material according to any one of claims 1 to 8 onto the silicon-containing resist intermediate film and then heat-treating the material; (II-4) forming a resist top layer film on the adhesion film using a photoresist material; (II-5) a step of forming a circuit pattern on the resist upper layer film by pattern-exposing the resist upper layer film and then developing the resist upper layer film with a developer; (II-6) A step of transferring the pattern to the adhesive film by dry etching using the resist upper layer film on which the circuit pattern is formed as a mask; (II-7) A step of transferring the pattern to the silicon-containing resist intermediate film by dry etching using the adhesion film on which the pattern is formed as a mask; (II-8) A step of transferring a pattern to the resist underlayer film by dry etching using the silicon-containing resist intermediate film to which the pattern has been transferred as a mask; and (II-9) a step of processing the substrate to be processed using the resist underlayer film to which the pattern has been transferred as a mask to form a pattern on the substrate to be processed; A pattern forming method comprising the steps of:
11. A method for forming a pattern on a workpiece substrate, comprising the steps of: (III-1) forming a resist underlayer film on a substrate to be processed; (III-2) forming an inorganic hard mask intermediate film selected from a silicon oxide film, a silicon nitride film, and a silicon oxynitride film on the resist underlayer film; (III-3) A step of forming an adhesion film by applying the adhesion film forming material according to any one of claims 1 to 8 onto the inorganic hard mask intermediate film and then heat-treating the material; (III-4) forming a resist top layer film on the adhesion film using a photoresist material; (III-5) a step of pattern-exposing the resist upper layer film and then developing it with a developer to form a circuit pattern on the resist upper layer film; (III-6) a step of transferring the pattern to the adhesive film by dry etching using the resist upper layer film on which the circuit pattern has been formed as a mask; (III-7) A step of transferring the pattern to the inorganic hard mask intermediate film by dry etching using the adhesion film on which the pattern is formed as a mask; (III-8) A step of transferring a pattern to the resist underlayer film by dry etching using the inorganic hard mask intermediate film to which the pattern has been transferred as a mask; and (III-9) a step of processing the substrate to be processed using the resist underlayer film to which the pattern has been transferred as a mask to form a pattern on the substrate to be processed; A pattern forming method comprising the steps of:
12. 12. The pattern formation method according to claim 11, wherein the inorganic hard mask intermediate film is formed by a CVD method or an ALD method.
13. 13. The method for forming a pattern according to claim 9, wherein a method for forming a circuit pattern on the resist upper layer film is performed by using photolithography having a wavelength of 10 nm or more and 300 nm or less, direct writing using an electron beam, nanoimprinting, or a combination thereof.
14. 14. The method for forming a pattern according to claim 9, wherein the development is carried out using an alkali development or an organic solvent.
15. 15. The pattern forming method according to claim 9, wherein the workpiece substrate is a semiconductor device substrate, or a semiconductor device substrate having any one of a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal oxide carbide film, and a metal oxide nitride film formed thereon.
16. 16. The pattern formation method according to claim 15, wherein the metal is silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum, or an alloy thereof.
17. A method for forming an adhesion film that functions as an adhesion layer used in a manufacturing process of a semiconductor device, comprising spin-coating an adhesion film-forming material according to any one of claims 1 to 8 onto a substrate to be processed, and heat-treating the substrate coated with the adhesion film-forming material at a temperature of 100°C or higher and 300°C or lower for 10 to 600 seconds to form a hardened film.
18. A method for forming an adhesion film that functions as an adhesion layer used in the manufacturing process of a semiconductor device, comprising spin-coating an adhesion film-forming material according to any one of claims 1 to 8 onto a substrate to be processed, and heat-treating the substrate coated with the adhesion film-forming material in an atmosphere having an oxygen concentration of 0.1% or more and 21% or less to form a hardened film.
19. A method for forming an adhesion film that functions as an adhesion layer used in the manufacturing process of a semiconductor device, comprising spin-coating an adhesion film-forming material according to any one of claims 1 to 8 onto a substrate to be processed, and heat-treating the substrate coated with the adhesion film-forming material in an atmosphere with an oxygen concentration of less than 0.1%, thereby forming a hardened film.
Citation Information
Patent Citations
Production of metal pipe coated with plastic
JP1979015982A
Soft contact lens
JP1982008521A
Liquid crystal display device
JP1982008522A
Resist underlayer film material and pattern forming method
JP2011164345A
Composition for forming organic film, substrate for manufacturing semiconductor device, method for forming organic film and pattern forming method
JP2019112584A